Case Report: Prosthetic revision due to aseptic loosening following total knee arthroplasty: a clinical management and pathological mechanism investigation - Li, Jun; Shang, He; Ma, Tao; Yang, Tianxiang; Wang, Yi; Liu, Xueqi; He, Xing; Ding, Yumei; Liang, Jinpeng; Wang, Yinbin; Chen, Desheng (Frontiers in Surgery, 2026)
BackgroundTotal joint arthroplasty is an effective treatment for end-stage joint diseases, with approximately 1.5 million procedures performed globally annually and a 25%–30% annual growth rate in China. However, 10%–15% of patients develop prosthetic loosening or subsidence within 15–20 years postoperatively, predominantly due to aseptic loosening (incidence >10%) caused by wear particle-induced aseptic inflammatory osteolysis. The role of autophagy in this pathogenesis remains incompletely understood.MethodsA 61-year-old female patient developed aseptic loosening 11 months after left total knee arthroplasty. Comprehensive management included preoperative screening (including synovial cell count, differential, and alpha-defensin detection), revision surgery (debridement of necrotic/inflammatory tissue/residual cement and implantation of a new prosthesis with vancomycin-impregnated cement), synovial HE staining, quantitative immunohistochemistry (IHC; Ki67, CD3, CD20, CD68, P62, LC3II, and Beclin1), and postoperative rehabilitation.ResultsPostoperatively, pain was relieved: the patient ambulated with crutches at 3 days, achieved 90° knee flexion at 1 week, and full pain-free weight-bearing (110° flexion) at 2 months. Postoperative infection markers (C-reactive protein and erythrocyte sedimentation rate) were temporarily elevated due to surgical trauma and returned to normal during follow-up. Imaging showed a stable prosthesis without infection or recurrent loosening. Synovial HE staining revealed extensive inflammatory infiltration; quantitative IHC showed high expression of inflammatory markers and low expression of autophagy-related markers. Clinical outcomes were favorable with validated patient-reported outcome measures (Knee injury and Osteoarthritis Outcome Score: 85 points; Western Ontario and McMaster Universities Osteoarthritis Index score: 20 points) at 6 months post-revision.ConclusionThe integrated protocol effectively treated aseptic loosening. Wear particle-induced chronic synovitis and altered autophagy-related marker expression may be involved in the pathogenesis, providing preliminary clinical and pathological evidence for further research.